A Comparative Study of Raja Isteri Pengiran Anak Saleha and Alvarado Scores to Diagnose Acute Appendicitis - Pachya, Uttam; Shrestha, Sita Ram; Pokharel, Yagya Raj; Thapa, Ambika (Journal of Nepal Health Research Council, 2021)
Background: Acute Appendicitis is a clinical diagnosis with atypical presentation in young, elderly, females, genitourinary and gynecological conditions. Delayed appendectomy increases the risk of appendicular perforation, sepsis morbidity and mortality. Literature reports as high as 20-40% negative appendectomy. Raja Isteri Pengiran Anak Saleha score has come with higher sensitivity and diagnostic accuracy than Alvarado score in Asian population. This study aims to compare RIPASA and Alvarado score for diagnostic accuracy. Methods: Appendectomy patients at Patan Hospital from April to September 2014 were compared on raja isteri pengiran anak saleha (cut-off value 7.5 out of 15) and Alvarado score (cut-off value 7 out of 10). Final diagnosis was histopathology based. Microsoft Excel and SPSS 17 were used for analysing sensitivity, specificity and diagnostic accuracy of both scores. The study included patients who underwent appendectomy with histopathology report and excluded those with conservative management, generalized peritonitis, appendicular lump and abscess. Results: There were 88 appendectomy patients with median age 26 (18.25, 35) years, and male 52 (59.1%). Negative appendectomy was 10 (11.36%). Sensitivity and specificity of Raja Isteri Pengiran Anak Saleha 98.71% and 80.00% respectively, and for Alvarado 52.56% and 70%.The Raja Isteri Pengiran Anak Saleha score had statistically significant sensitivity (p=0.000). Positive Predictive value, Negative Predictive Value and diagnostic accuracy were 97.46%, 88.89% and 96.6% for RIPASA and 93.18%, 15.19% and 54.4% for Alvarado respectively. Conclusions: The Raja Isteri Pengiran Anak Saleha score had better diagnostic accuracy compared to Alvarado score for diagnosis of Acute Appendicitis. Keywords: Acute appendicitis; alvarado score; RIPASA score